The path to European Monetary Union: An institutional economics approach - Siegfried Utzig (Intereconomics, 1991)
The planned broadening of the common internal market into an economic and monetary union as proposed in the Delors Plan means a significant qualitative leap in the process of European integration, which should ultimately lead to political union in Europe. Is this objective realistic? In what ways could it be achieved?
Keywords: 330; European Community